2020
DOI: 10.1101/2020.11.09.372375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nafamostat Mesylate in lipid carrier for nasal SARS-CoV2 titer reduction in a hamster model

Abstract: Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) has been responsible for the largest pandemic in recent decades. After seemingly being in control due to consequent lock-downs and social distancing, the majority of countries faces currently a second wave of exponentially increasing infections, hospital referrals and deaths due to SARS-CoV-2-mediated disease (COVID-19). To date, no effective vaccination has been found, and wearing masks and social distancing are the only effective approaches to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A single-dose pretreatment of Ad5- hACE2 -transduced mice and K18- hACE2 mice with 3 mg/kg of nafamostat intranasally delivered prior to inoculation with SARS-CoV-2 significantly reduced the viral titres over the study time course [ 26 ]. Furthermore, a study of 420 µg/mL of nafamostat suspended within a novel lipid formulation and administered intranasally to hamsters, which was immediately followed by inoculation with SARS-CoV-2, showed a transient but significant reduction in the viral load within the nasal cavity compared to controls [ 27 ]. Unfortunately, a histopathological assessment of the animals was not undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-dose pretreatment of Ad5- hACE2 -transduced mice and K18- hACE2 mice with 3 mg/kg of nafamostat intranasally delivered prior to inoculation with SARS-CoV-2 significantly reduced the viral titres over the study time course [ 26 ]. Furthermore, a study of 420 µg/mL of nafamostat suspended within a novel lipid formulation and administered intranasally to hamsters, which was immediately followed by inoculation with SARS-CoV-2, showed a transient but significant reduction in the viral load within the nasal cavity compared to controls [ 27 ]. Unfortunately, a histopathological assessment of the animals was not undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a histopathological assessment of the animals was not undertaken. Also, it is not possible to ascertain whether the limited benefit was a result of the formulation itself, since unformulated nafamostat was not used as a control [ 27 ]. However, studies with a primary lung epithelium cell model demonstrated the low cytotoxicity of the lipid formulation up to 6 µg/mL of nafamostat, with evidence of SARS-CoV-2 inhibition at this dose [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plitidepsin is a promising HDA, which targets the ubiquitously expressed elongation factor 1-alpha and has demonstrated high potency (ED = 1.62 nM and SI = 40.4) against SARS-CoV-2 infection in pneumocyte-like cells 21 . Cm and nafamostat mesylate are also HDAs targeting serine proteases, including host TTSPs, that are undergoing human trials against SARS-CoV-2; however, no significant protection against infection was observed in the adenovirus hACE2 model (Cm) or hamster model (nafamostat mesylate) of SARS-CoV-2 infection 4,51,52 . Recently reported clinical trial data for Cm treatment of hospitalized COVID-19 patients demonstrated a lack of impact on time to recovery and incidence of death following SARS-CoV-2 infection 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, no impact on pathology was reported. 25 It is not currently possible to ascertain whether the limited benefit were a result of the formulation itself since unformulated nafamostat was not used as a control in the published study. However, studies in a primary lung epithelium cell model did demonstrate low cytotoxicity of the lipid formulation up to 6 µg/mL nafamostat and evidence of SARS-CoV-2 inhibition at this dose.…”
Section: Discussionmentioning
confidence: 99%